UPAYA MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DENGAN PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) MELALUI MEDIA CANVA PADA MATA PELAJARAN SEJARAH INDONESIA KELAS XI IPA 1 SMAN 1 BANDAR SRIBHAWONO - Sari, Ernita; Riswanto, Riswanto; Rosa, Friska Octavia; Maryuning, Maryuning (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to increase students' interest in learning history. The learning design in this research uses the Project Based Learning (PjBL) model via Canva Media. The subjects of this research were 35 students. Data collection techniques were carried out systematically using observation sheets. Based on observations in the first cycle, students' interest in learning was included in the medium category with an average score of 4.29. In the second cycle, there was an increase in the average score obtained by students, namely 5.28 and continued with a significant increase in cycle III, namely with an average score of 6.62. With the findings and results of observations from the first cycle to the third cycle, there was a significant increase and reached the indicators set by the researcher. The results of this research prove that the application of the Project Based Learning (PjBL) model through Canva media can increase students' interest in learning. It is hoped that these findings can become a reference for teachers to increase students' interest in learning.